2016
DOI: 10.1160/th15-06-0520
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 gene mutations and coagulation-associated biomarkers

Abstract: Thromboembolic events are the second cause of death in cancer patients, although the mechanisms underlying this increased thromboembolic risk remain unclear. The aims of this study were to examine whether BRCA2 gene mutations may modify the circulating levels of thrombocoagulation biomarkers and whether breast cancer development may influence changes in such circulating biomarkers. The study was performed in 25 women with mutations in the BRCA2 gene (n=12 breast cancer, n=13 breast cancer-free) and in 13 BRCA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…54 The deficiency of GC has not been linked to trauma before, and may be involved in coagulation. 55,56 Similar to RBP4 and TTR, both TF and CP contain beta sheets amenable to common amyloid formation. 57 In contrast HPX (like CLU), could stabilize certain mis-folded plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…54 The deficiency of GC has not been linked to trauma before, and may be involved in coagulation. 55,56 Similar to RBP4 and TTR, both TF and CP contain beta sheets amenable to common amyloid formation. 57 In contrast HPX (like CLU), could stabilize certain mis-folded plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are also differences in protein expression between BRCA-positive women who have cancer compared with those who are cancer-free. 45,46 This literature, coupled with our results, suggests future research is warranted to better explore the relationship BRCA mutations may have with coagulopathy and ABR. Our study is mainly limited as a retrospective study.…”
Section: Discussionmentioning
confidence: 73%
“…BRCA status may be an important concern for plastic surgeons as previous literature has shown BRCA1/2 mutations are associated with changes in expression of thrombosis-related proteins including fibrinogen, vitamin D-binding protein, α1-antitrypsin, and others. 45,46 These changes are suggestive of increased coagulability and risk of thrombosis. Interestingly, there are also differences in protein expression between BRCA-positive women who have cancer compared with those who are cancer-free.…”
Section: Discussionmentioning
confidence: 99%
“…Because BRCA1/2 mediates DNA-repair and other vital pathways, it has been previously hypothesized that these genetic variants could be linked to other diseases. Indeed, several studies reported higher levels of proteins or biomarkers associated with elevated thrombotic risk in patients with BRCA1/2 mutations compared to controls with no mutations, independent of breast cancer [ 100 , 101 ]. These results suggest that the carriers of the mutations are prone to have coagulation-related problems independently of malignancies.…”
Section: Cardio-oncology Syndrome Type V (Cos 5): Systemic and Genetic Conditionsmentioning
confidence: 99%
“…These results suggest that the carriers of the mutations are prone to have coagulation-related problems independently of malignancies. Further, low levels of insulin-like growth factor 1 (IGF-1) were detected in individuals carrying BRCA1/2 mutations, while high levels of IGF-1 were detected in BRCA1/2 mutation carriers with breast cancer; abnormal concentrations of IGF-1 have been associated with higher risks to develop insulin resistance, which contributes to the pathophysiology of many CVDs [ 100 , 102 ].…”
Section: Cardio-oncology Syndrome Type V (Cos 5): Systemic and Genetic Conditionsmentioning
confidence: 99%